The Influence of Enterprise Risk Management on Firm Performance Measured by the Balanced Scorecard: Evidence from SMEs in Southern Thailand - Muttanachai Suttipun (Faculty of Social Sciences and Humanities, Chiang Mai University, 2020)
ASR (Asian Social Research) was first launched in 2014 by Chiang Mai University. However, it has a longer history, with its genesis in 2002 as part of Chiang Mai University Journal.This journal was split into two in 2007, with the formation of ASR's predecessor, the Chiang Mai University Journal of social Sciences and Humanities, which was later restyled as ASR in 2014, and began publishing online in 2015.